Emily Windsnap and the land of the midnight sun - Kessler, Liz (Kessler, Liz. Emily Windsnap., 2014)
Neptune, King of the ocean, sends half-mermaids Emily and Aaron to the land of the midnight sun to investigate the source of the dangerous storms brewing in the ocean.